Comprehensive genomic profiling of pediatric peritoneal mesothelioma: case report with a literature review - Jasmina Redzepagic (18767728) (2024)
Malignant peritoneal mesothelioma is an extremely rare and poorly recognized neoplasm in children. A 5-year-old boy presented with a 1-year history of progressive painless abdominal distension. A CT revealed a 19 × 19 × 11 cm3 cystic mass in the right hemiabdomen, without infiltrating the surrounding structures. The tumor was completely removed by surgery. The microscopic and immunohistochemical analyses confirmed peritoneal mesothelioma. Comprehensive genomic profiling revealed no major driving mutations including BAP1, no fusions, but with amplifications of AURKA, AURKC, HLA-1B, ZNF-217, OR5F1 and MEN1 genes. Imaging follow-up 3 months after surgery revealed metastatic disease. The patient died of pneumonia at another hospital shortly after the last follow-up examination at our institution. Pediatric peritoneal mesothelioma is an extremely rare malignancy with limited targeted options and a poor prognosis. Some of the identified molecular genomic biomarkers require further exploration and validation in this cancer. Other Information Published in: Journal of Surgical Case Reports License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/jscr/rjae324